2020
DOI: 10.1038/s41598-019-53999-1
|View full text |Cite
|
Sign up to set email alerts
|

Bile acid bio-nanoencapsulation improved drug targeted-delivery and pharmacological effects via cellular flux: 6-months diabetes preclinical study

Abstract: The antilipidemic drug, probucol (PB), has demonstrated potential applications in Type 2 diabetes (T2D) through its protective effects on pancreatic β-cells. pB has poor solubility and bioavailability, and despite attempts to improve its oral delivery, none has shown dramatic improvements in absorption or antidiabetic effects. Preliminary data has shown potential benefits from bile acid co-encapsulation with PB. One bile acid has shown best potential improvement of PB oral delivery (ursodeoxycholic acid, UDCA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 70 publications
7
40
0
Order By: Relevance
“…Previously, our studies have demonstrated that sodium alginate microcapsules significantly increase the brain uptake and associated neuroprotective effects of probucol-the highly lipophilic, antilipidemic drug [11]. Subsequent studies of ours confirmed that microencapsulation improves therapeutic efficiency of lipophilic drugs by protecting against degradation due to low stomach pH and efflux protein activity in the intestinal epithelium [12,13].…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…Previously, our studies have demonstrated that sodium alginate microcapsules significantly increase the brain uptake and associated neuroprotective effects of probucol-the highly lipophilic, antilipidemic drug [11]. Subsequent studies of ours confirmed that microencapsulation improves therapeutic efficiency of lipophilic drugs by protecting against degradation due to low stomach pH and efflux protein activity in the intestinal epithelium [12,13].…”
Section: Introductionsupporting
confidence: 56%
“…Bile acids promote aqueous solubility and increase fluidity of phospholipid membranes, making them ideal candidates for BBB permeability experiments [ 16 ]. A report from our lab showed that co-encapsulation with a DCA variant improved the targeted-delivery effects of probucol [ 12 ]. However, there is a relative paucity of studies focusing on the permeation effects of DCA on CBD absorption.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in IFN-γ and enhancement in IL-10 that the PB-ULCA microcapsules showed, are expected to decrease cell apoptosis and support cell function, which is supported by bioenergetics analysis [81]. Previously published data have displayed that the anti-oxidant activity of BAs enhanced β-cell viability [39,[81][82][83].…”
Section: Mechanical Strength Buoyancy Test and Drug Release Studiesmentioning
confidence: 71%
“…However, no significant difference was noted between the F1 and F2-treated cells in IFN-γ expression, possibly because of the different metabolic and secretory pathway compared to other cytokines [ 80 ]. The reduction in IFN-γ and enhancement in IL-10 that the PB–ULCA microcapsules showed, are expected to decrease cell apoptosis and support cell function, which is supported by bioenergetics analysis [ 81 ]. Previously published data have displayed that the anti-oxidant activity of BAs enhanced β-cell viability [ 39 , 81 , 82 , 83 ].…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation